Improved sieving of feces for cup sedimentation through use of a metallic sieve - Silva, Maria Ivani P. Gonçalves da (1981)
A 200-mesh per inch, stainless steel-aluminum grate adequately held by a metallic frame was found to be a good substitute for the usual discardable cotton gauze employed for sieving feces and similar material for parasitological examination. Besides being long Ias ting , its cleaning, desinfection and handling is easier. After testing different numbers of meshes per unit area, the 200-mesh per inch was compared with the standard surgical gauze in over 300 fecal specimens examined through cup sedimentation after sieving. More positive findings of eggs, helmin th larva e and protozoan cysts were obtained with the metallic grate.